Argentina and China : building a Sino-Latin American community with a shared future - Staiano, María Francesca (2025)
In this book, we humbly seek to contribute to the dialogue between China and Latin America to build a global community with a shared future, especially from an Argentinian perspective. We provided 12 chapters, divided into 3 sections. In Part I – Theoretical and Philosophical Foundations of the Community with a Shared Future – we introduce the conceptual and philosophical underpinnings of the "Community with a Shared Future” paradigm. In Part II – Global Governance, Law, and Inclusive Development – we explore the governance, legal, and developmental dimensions of China–Latin America cooperation, also taking into consideration geopolitical and strategic perspectives on the evolving multipolar order. In Part III – Culture, Identity, and Shared Representations – we focus on cultural exchanges and the soft power dimension.